Modeling the Long-Term Health and Cost Impacts of Reducing Smoking Prevalence through Tobacco Taxation in Ukraine - World Bank Group (World Bank, Washington, DC, 2017)
Smoking is a leading cause of preventable premature deaths. Smoking’s effects will continue to devastate lives in many countries, including Ukraine, if measures are not implemented to reduce its prevalence. Smoking is a major cause of many chronic diseases, such as cardiovascular disease, respiratory disease, and smoking-related cancers. Over recent years, successful tobacco control policies in Ukraine have resulted in one of the fastest declines in smoking prevalence in the world (1) This is largely due to multifaceted tobacco control legislation, adopted from 2005 and subsequently upgraded. Ukraine ratified the WHO Framework Convention on Tobacco Control (FCTC) in 2006. Currently, Ukrainian legislation basically corresponds to FCTC requirements. In 2005, Ukraine adopted a first tobacco-control law. Since then, several additional tobacco-control policies have been implemented in the country. Smoke-free policies supported by media campaigns have covered many workplaces and public places since the middle of 2006. Under these policies, at least 50 percent of the area of restaurants and bars had to be isolated from the smoking area, so that tobacco smoke did not penetrate into smoke-free areas. This measure was supported by an intensive media campaign and public movement in favor of smoke-free policies. Many restaurants went completely smoke-free both before and after implementing this measure. As of December 2012, restaurants, workplaces, and other public places became 100 percent smoke-free. Designated smoking places, which figured in the legislation between 2006 and 2012, were abolished in the amended laws. As of late 2006, cigarette packs carried textual warning labels covering 30 percent of their surface, in place of a previous warning which covered 10 percent of the front surface and stated: ‘Ministry of Health warns: smoking is bad for your health.’ Since October 4, 2012, large (50 percent of the pack surface area), graphic health-warning labels on tobacco packaging have been introduced. The present report provides evidence from a modeling exercise undertaken to predict the health and related cost impacts that may stem from the implementation of a tobacco excise tax increase in Ukraine. Impacts are calculated relative to the status quo before the tax hike, and are modeled, beginning in 2017, for 2025 and 2035.